Comparative studies on exposure of edible vegetables to spent engine oil and PAH components - Chidinma Ukachukwu; Angela Chika Udebuani; Tochukwu Nicholas Ugwu (Center for Science and Technology, IAIN Surakarta, 2023)
The consequences of enhanced PAH deposition and accumulation in food crop and other biota can be traced to environmental pollution through human activities which has improved due to industrial revolution. The impact of this phenomena has been observed in the food chain as this toxicant accumulates within its system and therefore, it can be exposed to human being with detrimental effect. The study compared exposure of edible vegetables to PAH from spent engine oil and three purchased PAH component (benzo(a)pyrene, benzo(k)fluoranthene and benzo(ghi)perylene). PAH was extracted from soil and plant using soxhlet extraction method. The health risk review was done using risk assessment model. The unpolluted vegetables showed a higher growth performance when compared to the exposed vegetables pertaining to their bio-tolerance. However, unpolluted vegetable was significantly different (P<0.05) from polluted vegetable. The result showed that Fluoranthene (Flu), benzo(a)Pyrene (B(a)P), Acenaphthene (Ace), Anthracene (Ant), Naphthalene (Nap) and Benzo(b)Fluoranthene obtained from spent engine oil polluted soil (SEOPS) were the most abundant in the soil. However, concentration of commercially purchased benzo(a)pyrene was observed to be higher in plants than (Benzo(k)fluoranthene and Benzo(ghi)perylene) utilized. Bioaccumulation factor total (BAFT) of commercially purchased B(a)P, B(k)F and B(ghi)P showed higher accumulation value (1.8, 1.5), compared to that of spent engine oil in edible vegetables. Analysis of the calculated assessing value (AV), Benzo(a)pyrene toxic equivalent quotient (BaPteq), food daily intake, and margin of exposure (MOE) showed potential risk concern when consumed, except for progressive lifetime cancer risk (PLCR). The PLCR poses relatively low health concern; nevertheless, prolonged exposure to these pollutants can affect humans as it possesses a high potential to bio-accumulate in edible vegetables.